An integrated investigation of the effects of ocean acidification on adult abalone (Haliotis tuberculata). (9th January 2020) - Avignon, Solène; Auzoux-Bordenave, Stéphanie; Martin, Sophie; Dubois, Philippe; Badou, Aïcha; Coheleach, Manon; Richard, Nicolas; Di Giglio, Sarah; Malet, Loïc; Servili, Arianna; Gaillard, Fanny; Huchette, Sylvain; et al.
Abstract: Ocean acidification (OA) and its subsequent changes in seawater carbonate chemistry are threatening the survival of calcifying organisms. Due to their use of calcium carbonate to build their shells, marine molluscs are particularly vulnerable. This study investigated the effect of CO2 -induced OA on adult European abalone ( Haliotis tuberculata ) using a multi-parameter approach. Biological (survival, growth), physiological (pHT of haemolymph, phagocytosis, metabolism, gene expression), and structural responses (shell strength, nano-indentation measurements, Scanning electron microscopy imaging of microstructure) were evaluated throughout a 5-month exposure to ambient (8.0) and low (7.7) pH conditions. During the first 2 months, the haemolymph pH was reduced, indicating that abalone do not compensate for the pH decrease of their internal fluid. Overall metabolism and immune status were not affected, suggesting that abalone maintain their vital functions when facing OA. However, after 4 months of exposure, adverse effects on shell growth, calcification, microstructure, and resistance were highlighted, whereas the haemolymph pH was compensated. Significant reduction in shell mechanical properties was revealed at pH 7.7, suggesting that OA altered the biomineral architecture leading to a more fragile shell. It is concluded that under lower pH, abalone metabolism is maintained at a cost to growth and shell integrity. This may impact both abalone ecology and aquaculture.